Flavonoid Role as Autophagy Modulators in Breast Cancer Treatment Strategy - Frans Dany; Ade Arsianti; Linda Erlina; Ratih Rinendyaputri (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2025)
Autophagy is a tightly regulated catabolic process that enables cancer cells to survive under metabolic stress and contributes to the development of chemoresistance. Targeting autophagy has therefore emerged as a promising strategy to enhance cancer therapy efficacy. Flavonoids, a diverse class of polyphenolic compounds abundantly found in plants, have gained considerable attention due to their broad-spectrum biological activities, including anticancer effects. Recent studies highlight their ability to modulate key signaling pathways involved in cell proliferation, apoptosis, and autophagy. Several flavonoids, such as fisetin, apigenin, and quercetin, exhibit roles as autophagy modulators depending on the cellular context, offering therapeutic flexibility. Their low toxicity and synergistic potential with conventional drugs underscore their relevance as adjuvant agents. This review discusses the critical role of autophagy in cancer progression and drug resistance, and examines current evidence supporting the integration of flavonoids as autophagy modulators in the design of more effective and targeted anticancer strategies, particularly in breast cancer therapy.